Security Challenges of Selective Forwarding Attack and Design a Secure ECDH-Based Authentication Protocol to Improve RPL Security - Haitham Y. Adarbah; Mostafa Farhadi Moghadam; Rolou Lyn Rodriguez Maata; Amirhossein Mohajerzadeh; Ali H. Al-Badi (IEEE Access, 2023)
Today, we could describe the Internet of Things (loT) as the pervasive and global network that provides a system for monitoring, controlling, processing, and analyzing the data generated by IoT devices. The huge amount of data generated by IoT devices when transported and routed through the internet presents several challenges. One of the common routing protocols in IoT networks is RPL (Routing Protocol for Low Power and Lossy Networks), but it is prone to security issues and attacks. Due to the presence of sensitive data in IoT and its exchange in the open network, issues of privacy and security in this network should be given special attention. In addition, the nodes in the Internet of Things have limited resources, and the symmetric encryption key is used to encrypt the data of all nodes, which has security weaknesses. Therefore, an efficient and secure authentication scheme is needed so that IoT nodes can authenticate each other and share a secure session key. In this article, we review security aspects of RPL protocols focusing on selective forwarding attacks. Further, we propose a key agreement and authentication mechanism based on ECDH (Elliptic-Curve Diffie–Hellman). We show that our design is very secure, that it meets security requirements, and that it can withstand known attacks while having low costs for computation and communication.